A Spin–Orbit‐Torque Memristive Device. (30th January 2019) - Zhang, Shuai; Luo, Shijiang; Xu, Nuo; Zou, Qiming; Song, Min; Yun, Jijun; Luo, Qiang; Guo, Zhe; Li, Ruofan; Tian, Weicheng; Li, Xin; Zhou, Hengan; et al.
Abstract: Memristors, demonstrated by solid‐state devices with continuously tunable resistance, have emerged as a new paradigm for self‐adaptive networks that require synapse‐like functions (artificial synapse, for example). Spin‐based memristors offer advantages over other types of memristors because of their significant endurance and high energy efficiency. Yet it remains a challenge to build dense and functional spintronic memristors with structures and materials that are compatible with existing ferromagnetic devices. Here, a memristive device based upon Ta/CoFeB/MgO heterostructures is demonstrated, which are commonly used in out‐of‐plane magnetized magnetic tunnel junctions (MTJ). To achieve the memristive function, a domain wall (DW) is driven back and forth in a continuous manner in the CoFeB layer by applying in‐plane positive or negative current pulses along the Ta layer, utilizing the spin–orbit torque (SOT) that the current exerts on the CoFeB magnetization. Hence, the magnetization and consequently the anomalous Hall effect (AHE) resistance are modulated in an analog manner, being controlled by the pulsed current characteristics including amplitude, duration, and repetition number. The quasi‐continuous AHE resistance variation is explained by the SOT‐induced DW creep motion. These results pave the way for developing SOT‐based energy‐efficient neuromorphic systems. Abstract : A memristive device based on a Ta/CoFeB/MgO heterostructure is demonstrated, utilizing spin–orbit torque (SOT) to drive a domain wall back and forth in the creep region. The anomalous Hall effect resistance can be modulated in an analog manner by the pulsed current characteristics including amplitude, polarity, duration, and repetition number, paving a way for developing SOT‐based energy‐efficient neuromorphic systems.